AVAC STRATEGY ON DETERMINANT VALUE CHAIN SUSTAINABLE COMPETITIVE ADVANTAGE - Guntarayana, Indria; Fawazi, Muhammad Halim; Afreliyansyah, Yogi (Media Inovasi Pendidikan dan Publikasi, 2024)
The increasingly modern consumer lifestyle influences purchasing decisions, so it aims to analyze the Determinant Marketing Capability Competitive Advantage at Angkringan in Blitar. This study uses mixed-methods, sampling was carried out on 100 Angkringan UMKM in Blitar, East Java. The results of the study show that Customer Relationship Marketing has a weak effect on Competitive Advantage, Marketing Capability is significant on Competitive Advantage, Marketing Capability plays a positive role with Customer Relationship Marketing, Marketing Capability is significant on Product Quality, Marketing Capability plays a positive role with Value Chain, Product Quality is not significant on Competitive Advantage, Value Chain is not significant on Competitive Advantage and is arranged in an AVAC strategy formulation.